A dynamic channel access strategy for underlay cognitive radio networks: Markov modelling and performance evaluation. Issue 1 (23rd February 2015) - Jalali, Elmira; Balapuwaduge, Indika A. M.; Li, Frank Y.; Pla, Vicent
Abstract: Unlike in overlay cognitive radio networks, secondary users in underlay cognitive radio networks can access licensed spectrum even at the presence of a primary user, given that the interference caused by the secondary transmission is lower than a pre‐specified threshold. Based on this underlay access principle, we propose in this paper a dynamic channel access strategy for multi‐channel cognitive radio networks. Different from existing underlay access techniques, channel assembling, spectrum adaptation and restricted channel occupancy are also considered in the proposed strategy in order to achieve better performance in the secondary network. Accordingly, a partial channel occupancy mode, which allows secondary users to access a portion of a channel when co‐existing with a primary user, is introduced in this study. The size of this portion is adjusted by selecting an appropriate value of a configurable parameter α in the partial channel occupancy mode. The system performance is evaluated for both primary and secondary networks, and a comparison analysis is carried out to assess the cost against the gain. Numerical results demonstrate that the proposed underlay channel access strategy outperforms the corresponding overlay strategy in terms of secondary network capacity, blocking probability and dropping probability. The cost and gain analysis identifies appropriate traffic conditions under which the overall system performance could be improved by employing the proposed underlay strategy. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper proposes a novel underlay channel access strategy for multi‐channel cognitive radio networks to enhance secondary network's performance, however, subjected to an interference constraint by the primary network. In the proposed strategy, we consider channel assembling and spectrum adaptation together with partial‐channel occupancy, which is characterised by a system configurable parameter, α ( 0 ≤ α ≤ 0 : 5 ) . The system performance is evaluated through Markov modelling for both primary and secondary networks in terms of several system‐centric parameters together with a cost against gain assessment.